Psikoedukasi Positive Parenting pada Pendamping dan Pembina UPTD KANRI Surabaya - Danu Aji Nugroho; Ika Yuniar Cahyanti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Caregivers and supervisors of UPTD KANRI Surabaya need to understand how the principles of caring to foster children. This study aims to see the effectiveness of positive parenting psychoeducation to increasing understanding of positive parenting. This research used quantitative experimental method by applying the one-group pretest-posttest design with a total of 9 caregivers & supervisors as subjects. The results show that this program is effective in increasing the subject s understanding of positive parenting. The increase can be seen from the difference in pretest & posttest scores and qualitative data. That knowledge will help subject to providing care to foster children.